Pest populations during the first six years in ryegrass pastures containing white or Caucasian clover - Watson, R.N.; Bell, N.L; Neville, F.J.; Davis, L.T. (New Zealand Plant Protection, 2000)
Insect and nematode pests in ryegrass pasture with white (WC) or Caucasian clover (CC) were similar in species composition In droughtprone soil however WC abundance fluctuated markedly over six years whereas CC was more persistent Insect pest populations in autumn followed similar overall time trends in each clover though some fluctuated less markedly in CC probably due to greater clover abundance and pasture cover rather than food quality differences Whitefringed weevil increased to damaging levels in CC by the sixth year Clover cyst nematode populations were suppressed by CC but root knot nematode increased to greater abundance than in WC soil Root knot nematode and whitefringed weevil may provide the greatest pest threats to longterm productive potential and persistence of CC in northern areas of New Zealand